Reingeniería de comercialización de la producción de frutos deshidratados para la empresa proalimentos Cotopaxi - Amón De la Guerra, Alex Rafael (2019)
The purpose of this research was to generate a proposal to improve the marketing of dried fruit company Proalimentos Cotopaxi by reengineering the production process. It was necessary to determine the basis of the sales process and online marketing company; identify processes that form and production times; as well as a market study which information collected company and its environment; ie, customers, competitors and the market in general. Reengineering marketing of dehydrated fruits was based on the survey method, in order to know the state that the product reaches the customer; also it consulted regarding the benefits of having online service and new payment methods such as bank transfers or payments with credit cards, showing an acceptance of 76% to new proposals for marketing and use of social networks, search engines, paid advertising per click (pay click), E-commerce. The study of the process and production times showed that a change in providers is necessary since the inspection of all bags of raw material, because of its poor quality, it generates a dead time 20 min per bag. 64% of respondents consume dried fruit which means that there is a significant demand for this product in the market.